The management of urban land in Ghana: the case of Accra and Kumasi Metropolitan Areas - Appiah, Williams Kofi (2015)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science in Development Policy and Planning,